Drivers of extreme wind events in Mexico for windpower applications. (7th October 2020) - Thomas, Simon Richard; Martínez‐Alvarado, Oscar; Drew, Daniel; Bloomfield, Hannah
Abstract: In this study, we use a k‐mean clustering approach to investigate the weather patterns responsible for extreme wind speed events throughout Mexico using 40 years of the ERA‐5 atmospheric reanalysis. Generally, we find a large geographical split between the weather patterns that generate the strongest winds across the country. The highest wind power production periods therefore occur at different times in different regions across the country. In the South, these are associated with cold surge events, where an anticyclone is present in the Gulf of Mexico resulting in a strong Northerly flow across the Isthmus of Tehuantepec. In the North‐East, Easterly trade winds are responsible for the strongest wind events, whereas in the North‐West, it is the proximity of the North Pacific High. However, the weakest winds and lowest power production periods occur at the same times for all stations with the exception of Baja California Sur, meaning that low wind power production may be unavoidable at these times. The El Niño Southern Oscillation is found to influence wind speeds at some locations across Mexico at sub‐seasonal time‐scales. We report that statistically stronger wind speeds are observed during the Summer during El Niño months than during La Niña months for both sites in Chiapas and Oaxaca. Abstract : The eight weather patterns obtained via k‐means cluster on the ERA‐5 reanalysis 500 hPa geopotential height over Mexico. The colour contours show the ERA‐5 mean‐sea level pressure with the black vectors showing winds. Weather patterns 1 and 8 are associated with the weakest winds across most of the country, whereas weather pattern 5 has the strongest, particularly for Chiapas and Oaxaca, where wind farms are located.